(untitled) (The Journal of Economic Concerns, 2024)
This study discusses the multifaceted impacts of climate change on Nepal’s environment, economy, and society. It highlights the country’s vulnerability to climate-related challenges such as erratic weather patterns, glacial melting, and the resulting socio-economic consequences for its population. The document also outlines Nepal’s efforts to address these challenges through policy frameworks like the National Climate Change Policy and the National Adaptation Programme of Action (NAPA). Additionally, it emphasizes the importance of international cooperation, community-based adaptation initiatives, and the promotion of renewable energy as key strategies to build resilience and mitigate the adverse effects of climate change in Nepal. The paper serves as a comprehensive resource for understanding the complexities of climate change in Nepal and the various measures being implemented to safeguard the country’s future. It provides valuable insights for policymakers, researchers, and development practitioners involved in climate action, emphasizing the need for a coordinated and multi-faceted approach to address the evolving impacts of climate change.